The effect of mold curing on the mechanical integrity of cold mix asphalt: a laboratory study from Marshall Stability perspective - Nazri, Nur’aina Syamimi; Ismail, Norfarah Nadia; Shaffie, Ekarizan; Wan Azahar, Wan Nur Aifa (Universiti Teknologi MARA, 2025)
Cold Mix Asphalt (CMA) is increasingly recognized for its environmental and economic advantages, yet its mechanical performance is still heavily reliant on the curing condition, an aspect often ignored in laboratory evaluations. A lack of standardized curing procedures during sample preparation has led to inconsistencies in performance assessments, making it difficult to compare results across studies or optimize mix designs effectively. This study presents a laboratory investigation in order to examine the impact of curing conditions on the mechanical integrity of CMA, with a particular focus on the mold curing process. CMA specimens were cured both inside and outside the Marshall mold to evaluate differences in mechanical performance as measured by the Marshall Stability test. It is found that specimens which underwent curing inside the mold have higher Marshall Stability value with 7.480kN as compared to 3.415kN for specimens that were cured outside of the mold. The results show a significant greater stability and durability for the specimens cured inside the mold due to enhanced cohesive development and the preservation of compaction. While this curing approach may not replicate actual field conditions, the findings are vital for improving laboratory protocols and ensuring accurate, reproducible evaluations of CMA formulations